Vehicle speed control using MRAC PID strategy for gradient disturbance rejection - Abdul Kadir, Faizul Akmar (2018)
Controlling vehicle speed is a challenging task,moreover when road gradient disturbance is taken into consideration.In this study,Model Reference Adaptive Control PID (MRAC PID) was proposed to handle the task. The study was conducted via simulation in MATLAB Simulink environment.Vehicle model used was constructed by combining validated Vehicle Longitudinal Model (VLM) and Electronic Throttle Body model (ETB) where VLM act as plant and ETB as the actuator.MRAC PID was utilized as the plant controller whereas Fixed Gain PID (FG PID) controls the actuator.A unique self-induced data was used as the Reference Model for the proposed controller together with MIT Rule as the adjustment mechanism.The performance of MRAC PID was studied by subjecting the vehicle to a set of gradient disturbances ranging from 0° to 25° with 5° increment at a driven speed of 90 kph.The results were compared against Gain Scheduling PID (GS PID) and FG PID control strategies.Simulation results shows that the proposed controller outperform the other controllers in both transient and disturbance region.HILS with Throttle-in-the-Loop was conducted as the means of validating the simulation results.It was observed that the simulations and HILS results shows similar pattern thus conclude that the results are valid.Several HILS data were collected for Repeatability Analysis.The Coefficient of Variance (CV) obtained from the analysis indicates that the HILS has high repeatability and well conducted.For future works,it is recommended that the actual torque curve from dynamometer test is used for the vehicle model and the braking effect is considered as it may offer better result as well as exploring several new actuators for HILS.